1998
DOI: 10.1104/pp.117.2.473
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Bypass of the Tricarboxylic Acid Cycle during Lipid Mobilization in Germinating Oilseeds1

Abstract: Upon germination of oilseeds, storage triacylglycerols are mobilized by conversion to carbohydrates for transport to the root and shoot axes of the developing seedling. Suc, the major carbohydrate transport form, is used as a substrate for biosynthesis and is respired for energy. Lipid mobilization in postgerminative oilseeds requires the metabolic coordination of four subcellular compartments: the oil body, the glyoxysome, the mitochondrion, and the cytosol (Trelease and Doman, 1984). The elucidation of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Although the molecular mechanism by which this inhibition occurs remains to be elucidated, the finding that seedlings lose their susceptibility to high sugar concentrations within approximately 48 h of the start of imbibition aids in developing possible models. For example, the timing with which Arabidopsis seedlings become resistant to high sugar concentrations is similar to the timing with which Brassica napus, a close relative of Arabidopsis, undergoes a dramatic metabolic shift (53). During the first 2 days after the start of imbibition, breakdown of B. napus seed storage lipids proceeds while the CO 2 -evolving reactions of the tricarboxylic acid cycle are bypassed.…”
Section: Discussionmentioning
confidence: 97%
“…Although the molecular mechanism by which this inhibition occurs remains to be elucidated, the finding that seedlings lose their susceptibility to high sugar concentrations within approximately 48 h of the start of imbibition aids in developing possible models. For example, the timing with which Arabidopsis seedlings become resistant to high sugar concentrations is similar to the timing with which Brassica napus, a close relative of Arabidopsis, undergoes a dramatic metabolic shift (53). During the first 2 days after the start of imbibition, breakdown of B. napus seed storage lipids proceeds while the CO 2 -evolving reactions of the tricarboxylic acid cycle are bypassed.…”
Section: Discussionmentioning
confidence: 97%
“…One possibility is that these apparently unused transcripts have been stored during quiescence, broken down after germination, and actively excluded from postgerminative translation. A study of the postgerminative induction of the TCA cycle enzyme isocitrate dehydrogenase also concluded that transcripts present before or shortly after germination were not translated (Falk et al, 1998), suggesting that this could be a general feature of the regulation of metabolism in germinating seeds. We hypothesize that the unused stored transcripts may themselves be a stored seed reserve that is broken down and the nucleotide components recycled for rapid de novo transcription during early postgerminative growth.…”
Section: Abi4 Is An Embryo-specific Regulator Of Tag Breakdownmentioning
confidence: 99%
“…23 Carbon flow through the full TCA cycle is delayed until the seedling is photosynthetically competent and no longer dependent on stored reserves. In the absence of exogenous sugars, the switch from autotrophic to phototrophic growth occurs in 2-3-day-old seedlings, 23 but in the presence of sucrose, lipid mobilization is retarded 24 and metabolic switching may be delayed. However, the effects of sucrose on lipid mobilization are not seen if sucrose is applied after 3 days.…”
Section: Gun1 May Optimize the Switch To Photoautotrophic Growthmentioning
confidence: 99%